THE USE OF RECIPROCAL TEACHING TECHNIQUE ON STUDENTS' ABILITY TO WRITE A SUMMARY ESSAY - Maulidda, Wida; Wahyuni, Asih; Sofia, Poppy (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
English learners needed to master the four key skills: reading,writing, speaking, and listening. The writing skill wasimportant for students to gather new information fromreading and to express their thoughts in writing.Consequently, teaching students to write paragraphseffectively required a suitable technique. This researchinvestigated the effect of the reciprocal teaching techniqueon students' ability to write summary essays. APre-Experimental method and One Group Pretest Posttestdesign were used in this research. The research targetedeleventh-grade students at SMA Rimba Madya, with asample of 29 students. Data collection involved pretests andposttests in the form of essay tests aimed at producingsummary essays with an introduction, body, and conclusion.Data were analyzed using the t-test. The pre-test resultsshowed that the highest score was 70, representing 17% ofthe sample, with five students achieving this score. Thelowest score was 35, representing 24% of the sample. Incontrast, post-test results improved with the highest scorereaching 90, again representing 17% of the sample, and thelowest score increasing to 55, representing 21% of thesample, with six students scoring at this level. The analysisrevealed a t-test value of 9, exceeding the t-table value of2.05 at the 0.05 significance level, leading to theacceptance of the alternative hypothesis (Ha). It could beconcluded that the reciprocal teaching technique had apositive effect on students' ability to write summary essays.